Early follow-up quality of life and mental health of patients with congenital vascular malformations cared for in a multi-disciplinary specialist centre. (March 2023) - Pang, Calver; Nisbet, Rebecca; Gibson, Michael; Evans, Nicholas; Khalifa, Mohamed; Papadopoulou, Anthie; Tsui, Janice; Hamilton, George; Brookes, Jocelyn; Lim, Chung Sim
Objective: The study aimed to evaluate the early follow-up quality of life (QoL), pain and mental health of patients with congenital vascular malformation (CVM) from a variety of treatment options. Methods: All patients with CVM who received care and had follow-up between February 1st 2018 and January 31st 2020 were included. The health-related QoL, pain, and mental health were assessed with RAND Health Care 36-Item Short Form Survey (SF-36), visual analogue score for pain (VAS-P) and Hospital Anxiety and Depression Scale (HADS). Paired t-test was used for all analyses. p < .05 were considered significant. Results: In total, 110 patients with a mean age of 36.9 years were included in this study. In all patients following care, significant improvement was found in the bodily pain domain of SF-36 and VAS-P (both p = .01). This was largely driven by high-flow vascular malformation patients who responded better to embolo-sclerotherapy, which revealed significant improvement in the bodily pain domain of SF-36 ( p = .002) and VAS-P ( p = .02). Patients who received supportive treatment only reported significant improvement in mental health ( p = .004) and social functioning ( p = .03) domains of SF-36. Meanwhile, patients treated with embolo-sclerotherapy reported significant improvement only in VAS-P ( p = .02). Conclusions: This study concluded that the effects of care on early follow-up QoL, pain and mental health of patients with CVM were heterogenous. Future research should therefore, include larger sample size and longer term follow-up to understand the various factors that affect the QoL and mental health of these patients, as well as the holistic approaches to manage them.